Answer:
0 < x < 3
Step-by-step explanation:
3 < x + 3 < 6 (Subtract 3 from all terms)
0 < x < 3 (The third option is the answer)
Answer:
(x - 5)^2 + y^2 = 225/4,
or you could write it as (x - 5)^2 + y^2 = 56.25.
Step-by-step explanation:
The factor form is
(x - h)^2 + (y - k)^2 = r^2 where the center is (h, k) and r = the radius.
So we have:
(x - 5)^2 + (y - 0)^2 = r^2
As the point (-1, 9/2) is on the line:
(-1 - 5)^2 + (9/2)^2 = r^2
r^2 = 36 + 81/4
r^2 = 225/4.
So substituting for r^2:
(x - 5)^2 + (y - 0)^2 = 225/4
(x - 5)^2 + y^2 = 225/4 is the standard form.
Answer:
-25
Step-by-step explanation:
10^2 ÷ -2^2 = -25
That's why the answer is -25.